A novel wound dressing material for full-thickness skin defects composed of a crosslinked acellular swim bladder - Zhang, Lifeng; Li, Yan; Jiang, Wei (Frontiers in Materials, 2022)
The repair of widely present skin-defects remains a daunting challenge. Previous researches have tackled the skin-defects by applying artificial skins which are nevertheless limited by high cost and complex fabrication. Biomaterials have attracted much attention in recent years attributed to their accessibility and excellent biocompatibility. Herein, we designed a novel cell scaffold material for wound dressing through swimming bladders, of which the mechanical properties could be enhanced by EDC/NHS cross-linking. Characterizations show that this material possesses many advantages including adequate porosity, high mechanical strength, and good thermal stability. Particularly, swimming bladders after EDC/NHS cross-linking have increased denaturation temperature and higher tensile strength, along with the capability for being colonized in the wound sites of rabbit models harmlessly, followed by rapid vascularization and cell growth with mild inflammatory reactions. The successful implantation of swimming bladders proves that this cell scaffold with unique features can be an outstanding wound dressing material.